Logo Design as Steps for the Existence of Kelulut Bee Honey (Trigona spp.) Into a Herbal Therapy Produced by Villagers at Beringin Village - Dewi Setya Paramitha (Borneo Community Development, 2021)
The potential of honey as an herbal therapy has no doubt about its benefits. Many local entrepreneurs saw the opportunity of cultivating local honey from the Trigona Spp. or it called kelulut bee honey as a promising business, however the farmer group at Beringin Village faces marketing obstacles. Product sale is limited to local buyers. The aim of this program was to build a branding image and increase sales of kelulut honey. The method used was to carry out community service by making a logo design on honey packaging and assisting marketing using social media. The results obtained were the creation of logos and packaging labels, and the dissemination of information about the products and cultivation of kelulut honey produced by Beringin Village on the Youtube channel and the Instagram. The promotion that has been carried out is expected to attract wider consumer interest, not only to increase sales but also as a new tourist spot to explore the location of kelulut bee honey cultivation. In the future, entrepreneurs can use digital media creatively and innovatively as a means of promotion. This activity is expected to become a government program so that it can increase regional income.